Implementación de una máquina trituradora para el reciclado del material de Tereftalato de Polietileno. - Bonilla Acurio, Wilson Stalin (2018)
The process of reuse of plastic bottles is one of the objectives that excel in the care of the environment, visualizing the purpose that can be given to this product the first step that is executed is the recycling of the same that are collected or buy storing in the centers of gathering, in containers or wineries, the large space that the plastic bottles occupy in their whole form has become a problem for the recyclers decreasing the physical space that is destined for the execution of this activity. Plastic bottles being made of polyethylene terephthalate (PET) is a material that is resistant to degradation directly affects the environment. Therefore, this project will implement a method of reducing the size of plastic bottles that will allow us to have greater storage capacity in the warehouses recycling, this can be done by implementing of a crushing machine of plastic bottles having an approximate crushing capacity of 40 Kg/h being the main objective of the shredder to reduce the size of the plastic bottles crushing in small pieces with a volume of 8mm. The Shredder is made up of different mechanical components such as the cutting tools that are the soul of the machine that are in charge of executing the crushing, axes, bearings, bearings among others, besides its electrical components of protection which will allow us to guarantee the operation of the machine. The handling of the shredding machine will be of a very low level of difficulty for the operator without the need of training directly benefiting it.